1984
DOI: 10.1128/jvi.50.2.478-488.1984
|View full text |Cite
|
Sign up to set email alerts
|

S1 nuclease mapping of viral RNAs from a temperature-sensitive transformation mutant of murine sarcoma virus

Abstract: The structures of murine sarcoma virus (MuSV) tsllO viral RNA and intracellular RNA present in MuSV tsllO-infected cells (6m2 cells) have been examined by S1 nuclease analysis. A previous study involving heteroduplex analysis of MuSV tsllO viral RNAs hybridized to wild-type DNA revealed the presence of two MuSV tsllO RNAs, 4.0 and 3.5 kilobases (kb) in length, containing overlapping central deletions relative to wild-type MuSV 124 viral RNA (Junghans et al., J. Mol. Biol. 161:229-255, 1982). Here we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 24 publications
6
43
0
Order By: Relevance
“…1). We have previously shown that the spliced 3.5-kb RNA will protect only 120 bases of the DD.29 DNA (11) (Fig. 4, lane 4), establishing that the gag gene in this RNA extends only up to the 5' splice site at nucleotide 2,017.…”
Section: Methodsmentioning
confidence: 80%
See 4 more Smart Citations
“…1). We have previously shown that the spliced 3.5-kb RNA will protect only 120 bases of the DD.29 DNA (11) (Fig. 4, lane 4), establishing that the gag gene in this RNA extends only up to the 5' splice site at nucleotide 2,017.…”
Section: Methodsmentioning
confidence: 80%
“…4, lane 4), establishing that the gag gene in this RNA extends only up to the 5' splice site at nucleotide 2,017. In contrast, the unprocessed 6m2 4.0-kb RNA will fully protect the DD.29 DNA fragment (11) (Fig. 4, lane 6).…”
Section: Methodsmentioning
confidence: 95%
See 3 more Smart Citations